Prevalence of Open Defecation Practice and Associated Factors Among Households in Geshiyaro Project Implementation Sites in Ethiopia: A Cross-Sectional Study - Zinabu Assefa Alemu; Ermias Alemayehu Adugna; Abel Weldetinsae Kidane; Aderajew Mekonnen Girmay; Mesay Getachew Weldegebriel; Badasa Wagari Likasa; Melaku Gizaw Serte; Kirubel Tesfaye Teklu; Tsigereda Assefa Alemayehu; Ewnetu Firdawek Liyew; Geremew Tasew; Zelalem Mehari; et al. (SAGE Publishing, 2024)
Background: Open defecation is a significant global challenge, impacting public health, environmental sanitation, and social well-being, especially in low- and middle-income countries like Ethiopia. It is the second-largest cause of disease burden worldwide by facilitating the spread of germs that cause diarrhea diseases. Studies examining open defecation practices are insufficient, especially in areas implementing Ethiopia's Geshiyaro project. Therefore, this study aimed to assess the status of open defecation practice and associated factors in the study area. Method: A community-based cross-sectional study was conducted from June to July 2023. The total number of households included in this study was 7995. A structured questionnaire and observational checklist were used to collect data. Descriptive and multivariate logistic regression analyses were performed using STATA version 16. Results: The study found that 16.5% of households practiced open defecation. The following factors were significantly associated with the occurrence of open defecation: residence (AOR = 1.56, 95% CI: 1.26-1.92), education (AOR = 0.59, 95% CI: 0.49-0.72), age (AOR = 0.53, 95% CI: 0.41-0.69), knowledge on diarrhea prevention (AOR = 1.32, 95% CI: 1.17-1.50), marital status (AOR = 1.61, 95% CI: 1.32-1.97), and awareness creation about WASH services (AOR = 1.96, 95% CI: 1.71-2.25). On the other hand, no significant association was observed between the occurrence of open defecation and the household's income (AOR = 1.07, 95% CI: 0.93-1.23) or the head of household sex (AOR = 0.94, 95% CI: 0.78-1.12). Conclusion: Open defecation remains a critical public health concern in Ethiopia's Geshiyaro project sites. Various factors influencing this practice have been identified. Targeted interventions are needed to enhance access to safe sanitation facilities and promote awareness of WASH services, aligning with SDG 3 target 3, and SDG 6 target 2.